School of Fear - Daneshvari, Gitty (Daneshvari, Gitty. School of fear (New York, N.Y.), 2009)
Twelve-year-olds Madeleine, Theo, and Lulu, and thirteen-year-old Garrison, are sent to a remote Massachusetts school to overcome their phobias, but tragedy strikes and the quartet must work together--with no adult assistance--to face their fears.